GEOLOGI, ALTERASI HIDROTERMAL DAN MINERALISASI DAERAH CIURUG DAN SEKITARNYA, KECAMATAN NANGGUNG, KABUPATEN BOGOR, PROVINSI JAWA BARAT - Mohammad Tommy Agus Binsar; Yoga Aribowo; Dian Agus Widiarso (Geological Engineering E-Journal, 2014)
The existence of metallic minerals in nature is closely related to geological conditions and hydrothermal alteration. hydrothermal alteration and mineralization occur due to hydrothermal solutions that change the physical and chemical properties of rocks and carrying metal elements which will be deposited on rock porosity and permeability have. hydrothermal alteration will make a special characteristic as an altered mineral association. Study of this alteration zone and mineralization will help us to make a plan for metal resources exploration. The purpose of this study was to determine the geological conditions study area include the morphology , lithology , structural geology , hydrothermal alteration zones , mineralization and determine the relationship between geology , hydrothermal alteration , and mineralization.Methods of research is using survey and analysis methods. Survey conducted by the method of data that collected in the field in the form of surface geological   mapping.   The   analysis   method     was     analysis    of    petrology, petrography, X-ray (XRD), and geological structure.Regional geomorphology of Ciurug Area classification based on Van Zuidam (1983) is divided into two units , namely units steep hilly volcanic landforms and volcanic landform units is very steep mountains. Lithology of the study area consists of older to younger andesite breccia , andesite lava, lapilli tuff , tuff , and andesite intrusion . Geological structure of the study area has a north-south direction . Hydrothermal alteration zones are present in the study area is the zone of argillic ( Illit - Kaolin ) , propylitic zone ( Smectite - Chlorite ) , and silicified zones ( Silica - Quartz ) . Mineralization in the area of research in the form of quartz veins and disseminated pyrite and chalcopyrite mineralization as ore deposits . Type of sediment deposition area of research   is  a   low   sulfidation epithermal type.